Program Edukasi Perlindungan Anak Tunarungu Terhadap Kekerasan Seksual - Wizerti Ariastuti Saleh; Nurul Mutahara; Syamsuddin; Tatiana Meidina; Zulfitrah (CV. Multi Kreasi Media, 2025)
Deaf children in Indonesia are more vulnerable to sexual abuse due to communication difficulties and a lack of knowledge about self-protection concepts. This community service programme aims to raise awareness about the prevention of sexual violence through a visual media and sign language-based education programme for deaf students at SLB-B YPPLB Makassar. Fifteen children and teachers took part in a one-day interactive training and socialisation activity involving a visual approach, sign language and hands-on practice. Pre- and post-test evaluation techniques showed a significant improvement in students' understanding, as evidenced by an increase in the average score from 3.5 to 10.7. Topics covered in the learning materials included identifying private body parts, recognising safe and unsafe touch, the different forms of sexual abuse (verbal, physical and digital) and reporting techniques. The main challenge lies in the insufficient involvement of parents and teachers. Continuous collaboration between schools, families and the community is necessary to achieve long-term results. This programme demonstrates the effectiveness of visual and sign language-based approaches in teaching deaf children about preventing sexual violence.